The etiology and management of dentinal hypersensitivity - Arua, Samuel O.; Fadare, Stephen A.; Adamu, VE (Orapuh Journal, 2021)
Dentin hypersensitivity involves loss of the tooth hard tissues leaving the dentin exposed with a short sharp pain response whenever it comes in contact with external stimuli. Above the cement-enamel junction (CEJ), loss of enamel causes dentin exposure. Below the CEJ, as soon as the cementum is exposed, it becomes non-viable and is lost, leaving the dentin exposed. When dentin hypersensitivity sets in, the patient feels so uncomfortable that they will avoid taking cold foods or brushing the affected tooth. Dentin hypersensitivity is a common tooth problem, especially with the growing demand for, and frequency of, tooth-whitening procedures. Bleaching-induced tooth sensitivity is becoming more common, although effective management options are available. We searched Google Scholar, Microsoft Academic, ProQuest, Cochrane Library, and Pubmed for information about dentin hypersensitivity. In this article, we have presented the following concepts about the condition: etiology, predisposing factors, signs and symptoms, epidemiology, as well as the correct diagnostic and treatment options for reversing the sensitivity impact and achieving optimal oral health.